The Use of Design Expert in Evaluating The Effect of pH, Temperature and Hydraulic Retention Time on Biological Sulphate Reduction in a Down-Flow Packed Bed Reactor - Chirwa, Evans M.N. (University of Pretoria, 2021)
Dissertation (MEng)--University of Pretoria, 2020.